Analisis Pengaruh Brand Image, Harga dan Promosi terhadap Keputusan Pembelian Air Minum Dalam Kemasan Merek Nestle Pure Life - Amirudin M Amin; Shania Natasha (Management Studies and Entrepreneurship Journal (MSEJ), 2020)
The need of water can no longer be avoided. Humans as living things need food and drink for survive. Likewise with animals and plants. Food is a major factor in meeting needs. But water is also an important factor in meeting human needs and other living needs. Everyday we consume water when eating, after exercising and doing activities. Communities in various places have water products that they consume. Every community choose bottled water products (AMDK) from various brands and types in their consumption. A variety of choices, practical, varied prices, to the benefits of people choosing bottled water. The purpose of this study is to find out and analyze the influence of Brand Image, Price and Promotion of Purchase Decisions of Nestle Pure Life Bottled Water (Case Study of Pelita Indonesia College Students in Pekanbaru). The method used is multiple linear regression analysis with a sample of 100 respondents. The reseach results showed that the Brand Image and Price does not have a significant effect on students decisions on Nestle Pure Life bottled water while the Promotion have a significant effect on student decisions. Keywords: Brand Image, Price, Promotion